Effect of PbO/CuO Addition to Microstructure and Electrical Properties of PLZT 9/65/35 - Apichart Limpichaipanit (2018)
© Taylor and Francis Group, LLC. PLZT (Pb0.91La0.09(Zr0.65Ti0.35)0.9775O3) ceramics can be prepared by sintering but it is difficult to obtain dense and transparent samples. In this study, PbO/CuO (where the ratio of PbO:CuO = 4:1) was used as a sintering aid to improve sinterability of PLZT. Glassy phase formation caused by the reaction between PbO and CuO promoted grain growth and densification. PLZT 9/65/35 + x wt% PbO/CuO (where x = 0, 1.0, 3.0 and 5.0) ceramics had relaxor ferroelectric behavior. Maximum dielectric constant at 1 kHz could be tailored to optimum condition when 1.0 wt% PbO/CuO was added and the ceramic was sintered at 1200°C (εr = 8370 and tan δ = 0.0093).